2016
DOI: 10.1016/j.neuroimage.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Vascular autorescaling of fMRI (VasA fMRI) improves sensitivity of population studies: A pilot study

Abstract: The blood oxygenation level-dependent (BOLD) signal is widely used for functional magnetic resonance imaging (fMRI) of brain function in health and disease. The statistical power of fMRI group studies is significantly hampered by high inter-subject variance due to differences in baseline vascular physiology. Several methods have been proposed to account for physiological vascularization differences between subjects and hence improve the sensitivity in group studies. However, these methods require the acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 81 publications
1
34
0
Order By: Relevance
“…Jahanian et al further showed that coefficient of variance (CV, standard deviation divided by mean) of the BOLD signal was significantly higher in hypertensive elderly subjects with chronic kidney disease than in young healthy volunteers (Jahanian et al, 2014). Other studies have explored a parameter that quantifying the degree of low-frequency variation of the BOLD signal, referred to as Amplitude of low-frequency fluctuations (ALFF), and have demonstrated a correlation between ALFF and hypercapnia-derived CVR (Di et al, 2013; Kazan et al, 2016). These methods have not attempted to differentiate various components of the BOLD signal, thus may contain a variety of physiological origins.…”
Section: Discussionmentioning
confidence: 99%
“…Jahanian et al further showed that coefficient of variance (CV, standard deviation divided by mean) of the BOLD signal was significantly higher in hypertensive elderly subjects with chronic kidney disease than in young healthy volunteers (Jahanian et al, 2014). Other studies have explored a parameter that quantifying the degree of low-frequency variation of the BOLD signal, referred to as Amplitude of low-frequency fluctuations (ALFF), and have demonstrated a correlation between ALFF and hypercapnia-derived CVR (Di et al, 2013; Kazan et al, 2016). These methods have not attempted to differentiate various components of the BOLD signal, thus may contain a variety of physiological origins.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one does not even need to acquire a separate resting-state scan here. In the same way that functional connectivity can be derived from the residuals of a General Linear Model (GLM) for task-based fMRI data [72], the amplitude of low frequency fluctuations in the residuals of task-based fMRI data (GLMres-ALFF) can also be used to rescale the BOLD signal change; this “vascular autorescaling” (VasA) technique was even shown to outperform RS-ALFF based normalization [73] (Figure 3(b)). Using data from the same fMRI run, as VasA does, is also desirable because it avoids contamination of the data with noise from a separate run.…”
Section: Validity: Are Individual Differences Attributable To Brain Fmentioning
confidence: 99%
“…(b) The ALFF of the residuals of task fMRI data (GLMres-ALFF) also looks very similar to RS-ALFF (left) and can be used to rescale the BOLD signal change (vascular autorescaling, or VasA). Figure modified with permission from [73]. (c) Decrease in BOLD response to a sensorimotor task as a function of increasing age in the occipital lobe (blue) is abolished after scaling the sensorimotor-task with RS-ALFF (red), where each point represents an individual.…”
Section: Figurementioning
confidence: 99%
“…Other means of RSFA-like estimates have been proposed for scaling BOLD activation data using fMRI BOLD data at different non-resting cognitive states, e.g. during task periods (Kazan et al, 2016) or fixation-/resting-periods succeeding task periods (Garrett et al, 2017). Given that short periods of cognitive engagement can modulate the BOLD signal in a subsequent resting state scan (Sami and Miall, 2013;Sami et al, 2014), future studies are required to generalise our findings to RSFAlike estimates derived from other types of fMRI BOLD acquisition.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%